IMPROVING STUDENTS' ABILITY IN WRITING REPORT TEXT BY USING THE THINK TALK WRITE STRATEGY - Batubara, Muhammad Hasyimsyah; Bastari, Umraini; Nurmalina, Nurmalina (Jurnal As-Salam, 2024)
This study intends to see the improvement of students' report text writing skills using the TTW strategy in Man 1 Central Aceh. The research design is experimental quantitative, while the data collection is by pre and post-test. The sample was taken from class XI IPA1 (20 students in an experimental class) and XI IPA2 (20 students in a control class). Before treatment, the writing ability of the experimental class students was low, with an average pre-test score of 34.65, while the control class students with an average score of 33.35. However, there was an increase after treatment in the experimental class, as seen from the average score results. The post-test average was 69.75, an increase of 35.1. The results of the t-test calculation, where the t-score value is greater than the t-table at a significance level of 0.05. It shows that (Ha) is accepted, and (H0) is rejected. It means that the TTW strategy contributes to improving student's writing skills in making report texts.